Quantification of food polysaccharide mixtures by 1H NMR. (1st January 2018) - Merkx, Donny W.H.; Westphal, Yvonne; van Velzen, Ewoud J.J.; Thakoer, Kavish V.; de Roo, Niels; van Duynhoven, John P.M.
Highlights: Combined method for the identification and absolute quantification of polysaccharides. Rapid, accurate and precise qNMR analysis of polysaccharide hydrolysates. Method accounts for non-instantaneous dissolution of polysaccharides. Included a time release function in the monosaccharide degradation factor. Adaptation of the monosaccharide degradation factor significantly influences pectin quantification. Abstract: Polysaccharides are food ingredients that critically determine rheological properties and shelf life. A qualitative and quantitative assessment on food-specific polysaccharide mixtures by 1 H NMR is presented. The method is based on the identification of intact polysaccharides, combined with a quantitative analysis of their monosaccharide constituents. Identification of the polysaccharides is achieved by 1 H NMR line shape fitting with pure compound spectra. The monomeric composition was determined using the Saeman hydrolysis procedure, followed by direct monosaccharide quantification by 1 H NMR. In the quantification, both the monosaccharide degradation during hydrolysis, as well as a correction for the non-instantaneous polysaccharide dissolution were taken into account. These factors were particularly important for the quantification of pectins. The method showed overall good repeatability (RSDr  = 4.1 ± 0.9%) and within-laboratory reproducibility (RSDR  = 6.1 ± 1.4%) for various food polysaccharides. Polysaccharide mixtures were quantitatively resolved by a non-negative least squares estimation, using identified polysaccharides and their molar monosaccharide stoichiometry as prior knowledge. The accuracy and precision of the presented method make it applicable to a wide range of food polysaccharide mixtures with complex and overlapping 1 H NMR spectra.